Transcultural adaptation of the EULAR activity index for primary Sjogren’s syndrome in Argentine - Secco, Anastasia (Eur J Rheumatol, 2020)
OBJECTIVE: To adapt the EULAR Activity Index for primary Sjögren’s syndrome (ESSDAI) to the Argentine population. METHODS: observational, cross-sectional study that included patients in a period of ten months. Three Argentine rheumatologists adapted and translated to Spanish the original version in English and the final version was translated back into English by a research associate whose mother language was English. In order to estimate the constructive validity of the index, the visual analogous scale (VAS) of disease activity was used by experts. A subgroup of patients attended a second visit in order to evaluate test–retest reliability. RESULTS: 51 patients were included, 49 (96.1%) were female, the median age was 58 ((interquartile range (IQR): 49–69)). The median global VAS was 10 (IQR: 4–22.25) and the median total ESSDAI score was 5 (IQR: 3–9). The correlation between the global VAS and the total ESSDAI score of the scale was 0.79. The intraclass correlation coefficient was 0.67 (95% CI: 0.32–0.92) for the total score and 0.98 (95% CI: 0.92–0.995) for the global VAS. The results of the correlation coefficient between the VAS and the scale for each domain were: constitutional symptoms: 0.46; lymphadenopathy: 0.76; glandular: 0.78; joint: 0.61; skin: 1; respiratory: 0.83; renal: 1; muscular:- (no patient had myositis); peripheral nervous system: 0.72; central nervous system: 0.67; hematological: 0.96; biomarkers: 0.86. CONCLUSION: The results of this study showed that the ESSDAI is a reliable and valid index for this pSS argentinian population.